2014
DOI: 10.1088/0951-7715/27/3/379
|View full text |Cite
|
Sign up to set email alerts
|

Spectral analysis of hyperbolic systems with singularities

Abstract: We study the statistical properties of a general class of two-dimensional hyperbolic systems with singularities by constructing Banach spaces on which the associated transfer operators are quasi-compact. When the map is mixing, the transfer operator has a spectral gap and many related statistical properties follow, such as exponential decay of correlations, the central limit theorem, the identification of Ruelle resonances, large deviation estimates and an almost-sure invariance principle. To demonstrate the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
123
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(123 citation statements)
references
References 54 publications
(108 reference statements)
0
123
0
Order By: Relevance
“…It follows from [DZ3,Lemma 5.3] that 1 B n,ε ν ∈ B w . In the proof of Lemma 3.4, it was shown that if x, y lie in different elements of M n 0 , then d n (x, y) ≥ ε 0 , where d n (·, ·) is the dynamical distance defined in (2.1).…”
mentioning
confidence: 99%
“…It follows from [DZ3,Lemma 5.3] that 1 B n,ε ν ∈ B w . In the proof of Lemma 3.4, it was shown that if x, y lie in different elements of M n 0 , then d n (x, y) ≥ ε 0 , where d n (·, ·) is the dynamical distance defined in (2.1).…”
mentioning
confidence: 99%
“…[DZ3] has the further problem that (H1) of that paper is not satisfied in the present setting. (H1) would require that the Jacobian of T κ,λ , which equals κλ, is large compared to the contraction obtained in the Lasota-Yorke inequalities, i.e.…”
mentioning
confidence: 87%
“…For systems with discontinuities, integrating on stable curves greatly simplifies the geometric arguments required to control the growth in complexity due to discontinuities. This was implemented first for two-dimensional piecewise hyperbolic maps (with bounded derivatives) [DL], and then for various classes of billiards [DZ1,DZ3] and their perturbations [DZ2]. It has also led to the recent proof of exponential mixing for some billiard flows [BDL].…”
Section: Introductionmentioning
confidence: 99%
“…Fix β > 0. Due to [1,Lemma 4.3], Lemma C.1, and the continuity in u provided by [16,Lemma 5.4] (see also Lemma 3.16 applied to L u,0 rather than P u ), we know that there exists C > 1 and α ∈ (0, 1) such that ∀n ∈ N * , sup β≤|u|≤π L n u,0 L(B,B) ≤ Cα n .…”
Section: 4mentioning
confidence: 99%